2005
DOI: 10.1002/app.22405
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PE/Binder/PA extrusion blow‐molded films. I. Heat sealing ability improvement using PE/EVA blends

Abstract: ABSTRACT:The optimization of three-layer films (PE/ binder/PA) manufactured by extrusion blow molding presents significant industrial challenges. The main issue consists in combining use properties (e.g., impermeability to water steam and oxygen, welding properties) with high mechanical, optical, and adhesion performances, while maintaining cost-effectiveness. This article shows that the introduction of EVA in the PE layer improves the heat sealing ability and optical properties without degradation of the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…In contrast, peelable PE seals necessitate sealant modifications, typically addition of an immiscible and lower softening temperature polymer-such as polybutylene, methyl acrylic acid or methyl acrylate ethylene-copolymers, ionomers, and/or EVA copolymers. [5,6] Such blends, beyond the obvious decrease in seal initiation temperature, also lead to an apparent reduction in area of bonding, and thus to reduced seal strengths. This affords for peelable seal strengths to form over a broader temperature range (5 to 15 8C wide) compared to the much narrower (less than 5 8C wide) range for the respective PE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, peelable PE seals necessitate sealant modifications, typically addition of an immiscible and lower softening temperature polymer-such as polybutylene, methyl acrylic acid or methyl acrylate ethylene-copolymers, ionomers, and/or EVA copolymers. [5,6] Such blends, beyond the obvious decrease in seal initiation temperature, also lead to an apparent reduction in area of bonding, and thus to reduced seal strengths. This affords for peelable seal strengths to form over a broader temperature range (5 to 15 8C wide) compared to the much narrower (less than 5 8C wide) range for the respective PE.…”
Section: Resultsmentioning
confidence: 99%
“…Empirically, [12,13] a seal strength of 0.77 N per cm width of seal (ca. 200 g Á inch À1 ) is considered as the onset of hermetic seal formation, [6,7] heat sealing curve, progressing with increasing temperature from noseal (seal strength below 1 N Á cm À1 ), to peelable seals over a narrow temperature range, to weld/fused seals at higher temperatures. (b) The PE/EVA/MMT achieves peelable heat seals over a very broad range of sealing temperatures, [14] independent of the substrate sealed on.…”
Section: Resultsmentioning
confidence: 99%
“…As the addition of EVA increased, the heat sealing strength rose. EVA has a high ratio of the amorphous phase, which caused the 2 heat sealing layers to more easily penetrate each other during the coextrusion process and their molecular chains to tangle more closely together . As the EVA amount increased, the amorphous region was enlarged.…”
Section: Resultsmentioning
confidence: 99%
“…13 heat sealing layers to more easily penetrate each other during the coextrusion process and their molecular chains to tangle more closely together. 34 As the EVA amount increased, the amorphous region was enlarged. Therefore, the heat sealing strength increased.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…However, studies on correlation of physical properties and final seal performance of LDPE/EVA blends in open literature are limited. Studies on PE/EVA blends in amultilayer structure showed the effect of incorporating al ow content vinyl acetate EVA (9 %) in seal layer and tie layer (Poisson et al, 2006a;Poisson et al, 2006b;Zhang et al, 2009). In this work we investigate the effect of EVA incorporation in monolayerPEsealant for several compositions produced by the film blowing process.…”
mentioning
confidence: 99%